2011
DOI: 10.1099/ijs.0.019380-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarboniphaga daqingensis sp. nov., isolated from a freshwater lake

Abstract: A Gram-negative bacterium, designated B2-9 T , was isolated from water of a slightly alkaline lake, Longhu Lake in Daqing, north-east China. Strain B2-9T was an aerobic rod, heterotrophic, catalase-and oxidase-positive and motile by means of a single polar flagellum. The isolate grew well on n-alkanes C 9 -C 17 and weakly on C 6 -C 8 , C 18 and C 19 . Growth occurred at 10-37 6C (optimum 20-25 6C), at pH 5.5-9.5 (optimum pH 7.0) and with ¡1.0 % (w/v) NaCl. The major fatty acids were C 18 : 1 v7c (41.4 %), summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…(Palleroni et al, 2004) cultivated the strain Hydrocarboniphaga effusa DSM 16095 T successfully that originally was isolated from soil contaminated with heavy fuel oil hydrocarbons in New Jersey. Recently, Liu et al (2011) linked another strain, Hydrocarboniphaga daqingensis NBRC 104238 T to degradation of alkanes with medium chain length (C 9 –C 17 ). Additionally, some representative sequences from soils with amendment of C1 or C2 could be linked to the genus Thalassolituus , which is closely related to alkB sequences of Pseudomonas.…”
Section: Discussionmentioning
confidence: 99%
“…(Palleroni et al, 2004) cultivated the strain Hydrocarboniphaga effusa DSM 16095 T successfully that originally was isolated from soil contaminated with heavy fuel oil hydrocarbons in New Jersey. Recently, Liu et al (2011) linked another strain, Hydrocarboniphaga daqingensis NBRC 104238 T to degradation of alkanes with medium chain length (C 9 –C 17 ). Additionally, some representative sequences from soils with amendment of C1 or C2 could be linked to the genus Thalassolituus , which is closely related to alkB sequences of Pseudomonas.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies on the composition of soil microbial diversity in saline soils revealed that soil salinization had negative effects not merely on soil biochemical properties, but also on the structure of microbial communities (Foti et al, 2007;Yuan et al, 2007;Hidri et al, 2013;Wang et al, 2014;Zhang et al, 2015). Regarding the soil microbial community in saline soils of Songnen Plain, only some representative new species of halophilic and halotolerant bacteria and archaea have been reported by pure culture methods (Wu et al, 2008;Wang et al, 2010;Liu et al, 2011b;He et al, 2014;Pan et al, 2016). These microorganisms have gradually formed adaptations, including unique structures and physiological functions, such as the accumulation of osmotic adjustment-related substances (Yan and Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…eff use (Palleroni et al, 2004) and H . daqingensis (Liu et al, 2011), were reportedly capable of degrading n -alkanes. Similar results were also reported for the phylotype affi liated with the family Comamonadaceae, which contained functional genera capable of degrading n -alkanes and cyclic alkanes (Brzostowicz et al, 2005;Mattes et al, 2008).…”
Section: Phylogenetic Analysis and Diversity Of Bacterial Communitiesmentioning
confidence: 99%